PREVALENSI, KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN PATIN YANG DIBERI PAKAN MENGANDUNG DAUN JAMBU BIJI (Psidium guajava) DAN DIINFEKSI Aeromonas hydrophila - Matrilesi .; Ade Dwi Sasanti; Muslim . (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACT In fish cultivation, Aeromonas hydrophila could couse desease epidemic with mortality rate of 80-100% for 1-2 weeks. The purpose of research was to know the effect of addition of guava leaf in feed to prevalence, survival rate and growth of pangasidae which infected by A. hydrophila. The research was conducted on August- September 2015 in Laboratorium Budidaya Perairan and UPT. Klinik Kesehatan, Sriwijaya University. The research used Completed Randomized Design (CRD) with  six treatments and three replications, there were fish fed commercial feed and infected by A. hydrophila, fish fed by commercial feed with addition of guava leaf powder 1.5%, 2%, 2.5%, 3%, 3.5% and infected. The result of the research showed the addition of guava leaf to feed has a significant effect to prevalence and survival rate of pangasidae, but has n’t have significant effect to growth of pangasidae. The treatment on P1 has the best result with prevalance 42.22%, survival rate 75%, absolute weight 6.34 g and absolute length 2.41 cm. Keywords : Aeromonas hydrophila, Bacteria infected, Guava leaf, Pangasidae